“Never break them in two. Never put one over the other. Eve is Mary’s mother. Mary is the daughter of Eve”: Toni Morrison’s Womanist Gospel of Self - Claude LE FUSTEC (E-REA)
Carefully following the chronology of Toni Morrison’s novels until Paradise (1997), this article focuses on Morrison’s rewriting of the Fall as the American “grand narrative” and basis of a powerful sexist and racist ideology via a number of black female characters variously characterized as outcasts. From Pecola, the alienated victim of the WASP definition of beauty to Consolata, the “revised Reverend Mother,” Morrison’s fiction appears to weave its way through the moral complexities of African American female resistance to white male rule—theologically based on the canonical reading of the Fall as supreme calamity caused by Eve, the arch-temptress and sinner—to hand authority back to the pariah and wrongdoer: the black woman. However, far from boiling down to this deconstructive strategy, Morrison’s fiction seems to oppose religious doctrine only so as to sound the ontological depth of Christianity: while challenging the theological basis of sexist and racist assumptions, Morrison poses as an authoritative spiritual force able to craft her own Gospel of Self, based on cathartic moments of revelation where mostly female characters experience a mystic sense of connectedness to self and other, time and place. An African American female variation on the New Testament’s “Kingdom within,” Morrison’s novels echo black abolitionist Sojourner Truth’s famous speech “Ain’t I a Woman?” and its call for theological revision and gender emancipation.